MANAJEMEN RISIKO TSUNAMI UNTUK PENATAAN RUANG DI PESISIR PERKOTAAN PACITAN JAWA TIMUR - Ratih Probosiwi (Jurnal Teknosains, 2013)
The process of tsunami risk management through the use of disaster information is the important things to carry out by government of region with high potential tsunami hazard such as urban areas of Pacitan. Assessment of tsunami risk begins from hazard assessment, vulnerability and capacity assessment will provide appropriate information and also support decision making processes in order to reduce risk and loss that might arise when the disaster actually occurs. The policies of tsunami risk reduction could be done by spatial planning policy to regulate and control land usage in The Urban Pacitan. This article describes how the tsunami risk management for spatial planning done by the Pacitan Government.